ANALISIS NILAI-NILAI PSIKOLOGIS HUKUM ISLAM DALAM SEDEKAH - Irsan; Khairunnas Jamal; Muhammad Nurul Fahmi (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
This study analyzes psychological values of alms in shari'a. This research is a library research, and the data analysis technique in this research is content analysis. This study concludes that the psychological values of Islamic Law are the psychological values, thoughts and behaviors contained in each Shari'a in Islam, whether the Shari'a is in the form of words or deeds. This research also concludes that the psychological values contained in the Shari'a regarding wills are the motivation to always be think good of Allah, the motivation to always be enthusiastic at work, the motivation to always be empathetic to others, the motivation to always be a person with a big heart, the motivation to always be pious individual.